Wind tunnel study of different roof geometry configurations for wind induced natural ventilation into stairwell in tropical climate - Moey, Lip Kean; Adam, Nor Mariah; Ahmad, Kamarul Arifin; Abdullah, Luqman Chuah (Research India Publications, 2018)
Demand on buildings is in increasing trend all over the world as human population increases. This subsequently increases the electricity consumption and result in more greenhouse gases release to the atmosphere causing global warming. Natural ventilation is an effective method to reduce building electricity consumption. In this study, two types of roof namely flat surface roof and ellipse surface roof were investigated through wind tunnel experiment to evaluate the ventilation performance of a stairwell in tropical climate. The incoming wind speed of range 1 m/s to 5 m/s is set in the wind tunnel to simulate the wind speed in Malaysia. The wind speed of all openings for the reduced stairwell model is of the main concern because higher wind speed will lead to higher air change rate (ACH), which is the criteria to assess the natural ventilation performance of a building. Results have indicated that the measured air speed at inlets and outlets are higher for ellipse surface roof as compared to those of the flat surface roof. The measured air speed difference is more than 22.8% on outlet openings for ellipse surface roof when the incoming wind speed is 2-5 m/s. The study indicates that roof design configuration has an impact on ventilation performance in tropical climate as the temperature difference between inside and outside is negligible.